Anti-vascular Endothelial Growth Factor Outpatient Treatment Patterns in Patients with Exudative Age-related Macular Degeneration from a Japanese Hospital Claims Database - Tomohiro Iida; Aya Narimatsu; Kenji Adachi; Edward CY Wang (Journal of Health Economics and Outcomes Research)
**Purpose:** To identify outpatient treatment patterns of patients with exudative age-related macular degeneration (AMD) who received approved anti–vascular endothelial growth factor (VEGF) therapy, using real-world data from hospitals in Japan.